The Effect of Strength-Based Parenting, Religious Commitment, Demographic Factors Mediated by Positive Affect on Students' Character Strength - Dewitri Ulfha Ratnasari (‎‎‎TAZKIYA Journal of Psychology, 2023)
This study aims to determine the effect of strength-based parenting and religious commitment on students' character strengths mediated by positive affect. This study uses quantitative methods. The sampling technique was a non-probability and purposive sampling technique. The subjects of this study were 484 students of Senior High School X. The scale used is VIA-72, SBP scale, MUDRAS, and NAPAS. Data were analyzed by path analysis technique using Lisrel 8.80. Based on the results of the analysis showed that the model "the influence of strength-based parenting and religious commitment on the strength of students' character is mediated by positive affect" fits the data. Positive affect acts as a mediator for the dimensions of strength-based parenting use, engaging in bodily worship of Allah, and recommended acts except for strength-based parenting knowledge and sinful acts. Parents can start bonding-based parenting by keeping a diary of the strengths their children use on a daily basis, mapping out the strengths of each family member, and asking questions about the strengths their children have.